Self-harm, substance use and psychological distress in the Australian general population - Moller, C.; Tait, Robert; Byrne, D. (Wiley-Blackwell Publishing Ltd., 2013)
AIMS: To examine predictors of self-harm, especially substance use and psychological distress, in an Australian adult general population sample.DESIGN: Sequential-cohort design with follow-up every four years.SETTING: Australian general population.PARTICIPANTS: A random sample of adults aged 20-24 and 40-44 years (at baseline) living in and around the Australian Capital Territory.MEASUREMENTS: Self-report survey including items on four common forms of self-harm. Psychological distress was indexed by the combined Goldberg Anxiety and Depression scale scores and alcohol problems by the Alcohol Use Disorders Identification Test (AUDIT).FINDINGS: Four thousand one hundred and sixty people (84% of baseline) were re-interviewed at 8 years: 4126 reported their self-harm status. Past year self-harm was reported by 8.2% (95% CI 7.4-9.0%) of participants [males: 9.3% (8.0-10.6%), females: 7.3% (6.2-8.4%)]. Several forms of substance use-smoking (OR = 1.52), marijuana use (OR = 1.77) and drinking alcohol at a level likely to cause dependence (AUDIT score = 20) (OR = 2.08)-were independently predictive of past year self-harm. Additional key risk factors for self-harm in the past year were childhood sexual abuse by a parent (OR = 3.07), bisexual orientation (OR = 2.65), younger age (OR = 2.23) and male gender (OR = 1.86). Other independent predictors were years of education, adverse life events, psychological distress and financial strain.CONCLUSIONS: Self-harm in young and middle-aged adults appears to be associated with current smoking, marijuana and 'dependent' alcohol use. Other independent predictors include younger age, male gender, bisexual orientation, financial strain, education level, psychological distress, adverse life events and sexual abuse by a parent